2020
DOI: 10.2323/jgam.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of glycolipid MPIase (membrane protein integrase) is independent of the genes for ECA (enterobacterial common antigen)

Abstract: From these results, we conclude that the biosynthetic genes for MPIase and ECA are independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…We identified five genes that fit these criteria: elyC , ynbB , ymiB , lapA , and yoaI ( Table S2 ). From these hits, we confirmed the data in the literature that ynbB was not necessary for the synthesis of ECA PG ( 68 ; unpublished data).…”
Section: Resultssupporting
confidence: 87%
“…We identified five genes that fit these criteria: elyC , ynbB , ymiB , lapA , and yoaI ( Table S2 ). From these hits, we confirmed the data in the literature that ynbB was not necessary for the synthesis of ECA PG ( 68 ; unpublished data).…”
Section: Resultssupporting
confidence: 87%
“…The synthesis of MPIase has previously been shown to be independent of ECA synthesis (81) and our results confirm that these molecules use distinct lipid donors. The ECA genes necessary for biosynthesis of the ECA sugars and the formation of the ECA chain has also been shown to be dispensable for MPIase formation (81), although later results suggest they may contribute to some extent (82). Exploring the differences and similarities between these biosynthetic pathways will provide interesting insights into both pathways.…”
Section: Discussionsupporting
confidence: 87%
“…It has been shown that MPIase is important for driving integration of membrane proteins into the IM, and also Sec‐dependent translocation of periplasmic and OM proteins across the membrane (Nishiyama et al ., 2012; Sawasato et al ., 2019b). MPIase biosynthesis has been shown to require the activity of CdsA (Sawasato et al ., 2019a), the CDP‐diacylglycerol synthase critical for PL synthesis; however, despite the identical trisaccharide units, this process appears to be independent of the ECA pathway (Kamemoto et al ., 2020). Consequently, it is not clear how and why DAG‐PP‐linked species, the presumed precursors to MPIase, would accumulate in ECA biosynthesis mutants.…”
Section: Discussionmentioning
confidence: 99%